(untitled) (Research, Society and Development, 2024)
This research proposes an innovative didactic approach, integrating the opportunities offered by the Hybrid Teaching model with David Ausubel’s theory of Meaningful Learning. This proposal, based on the theoretical-practical learning modality, is based on the cognitivist perspective of knowledge. That said, the central objective of this article is to explore how a Didactic Proposal, based on the Hybrid Teaching methodology and the Theory of Meaningful Learning, can play a crucial role in the teaching and learning process in Financial Mathematics for students in the modality Youth Education and Adults (YEA). The study, of a qualitative nature, was conducted through field research, carried out in an YEA class at the Joaquim Gomes Crespo State School, located in the municipality of São Francisco do Itabapona, in the State of Rio de Janeiro. Data collection included questionnaires, assessments carried out before, during and after the implementation of the proposal, in addition to the students’ own records. The data collected aimed to explore students’ performance and reactions in relation to Financial Mathematics concepts. The results consistently revealed that the adopted methodology played a significant role in the improvement and effective learning in Financial Mathematics for students from the YEA. This finding highlights the effectiveness and relevance of the integration between Hybrid Teaching and Meaningful Learning as an enriching pedagogical approach for this specific audience.